Inhalational Induction of General Anaesthesia for Elective Caesarean: Ethical Acceptability in Treatment-resistant Needle Phobia?. Issue 2 (June 2021) - Parrott, N.; Prabhu, P.; Yeow, C.
Abstract : ( Int J Obstet Anesthesia . 2020;43:27–29) This case study describes the cesarean delivery of a woman with a severe needle phobia, which led her to decline regional anesthesia, IV access, or other processes involving needles while awake. The patient previously underwent general anesthesia for an emergency cesarean delivery and requested inhalational induction of anesthesia for her elective repeat cesarean.